The fourteen luminaries of Islam: biography of Prophet Muhammad (S.A.W.), Hadrat Fatima Zahra (A.S.), and the Twelve Holy Imams (A.S.) - Ahmad Ahmadi Birjandi (Islamic Research Foundations, 2011)
tr,1/dw c.1